2017
DOI: 10.1164/rccm.201702-0278oc
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Point-of-Care Xpert MTB/RIF on Tuberculosis Treatment Initiation. A Cluster-randomized Trial

Abstract: Scientific Knowledge on the SubjectCentralised laboratory-based diagnostic systems for tuberculosis are associated with substantial loss to follow-up and delays prior to treatment. Whether decentralised, point-of-care diagnostic systems can reduce loss to follow-up and treatment delay has not been adequately investigated. What This Study Adds to the FieldThis is the first randomised trial to make a direct comparison between point-of-care and laboratory use of a molecular TB diagnostic. The point-of-care strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Molecular testing methods result in more rapid laboratory turnaround times, 12 , 68–70 and are therefore likely to reduce time to treatment. This was confirmed in our analysis, with genotypic testing resulting in significantly shorter time to treatment than phenotypic methods; our findings are consistent with the results of a randomized trial 71 and a retrospective cohort study published after our search was concluded. 72 Xpert is of particular interest due to the feasibility of testing in peripheral laboratories, 73 , 74 potentially reducing reliance on transport and resulting in more rapid communication of results.…”
Section: Discussionsupporting
confidence: 90%
“…Molecular testing methods result in more rapid laboratory turnaround times, 12 , 68–70 and are therefore likely to reduce time to treatment. This was confirmed in our analysis, with genotypic testing resulting in significantly shorter time to treatment than phenotypic methods; our findings are consistent with the results of a randomized trial 71 and a retrospective cohort study published after our search was concluded. 72 Xpert is of particular interest due to the feasibility of testing in peripheral laboratories, 73 , 74 potentially reducing reliance on transport and resulting in more rapid communication of results.…”
Section: Discussionsupporting
confidence: 90%
“…This may be because time to treatment initiation has decreased with health systems changes, including introduction of the Xpert MTB/RIF rapid diagnostic (53,54). We did not identify any factors associated with risk of mixed infection and contrary to previous studies did not detect worse outcomes in patients with mixed infection, although we compared sixmonth rather than end of treatment outcome and our studies were heavily weighted for patients with DR-TB.…”
Section: Discussionmentioning
confidence: 62%
“…In the Journal, Lessells et al reported the results of a cluster randomised-controlled trial examining the impact of point-of-care compared to hospital laboratory implementation of Xpert MTB/RIF, a molecular test for TB and rifampicin resistance(10), on TB treatment initiation among individuals who were either HIV positive (92.5%), and/or had risk-factors for MDR-TB (45%) (11). There was no difference between the point-of-care and laboratory arms in the primary outcome of the proportion of The WHO has recently endorsed the new Xpert Ultra assay as an alternative to Xpert MTB/RIF (12).…”
Section: Diagnosis and Treatment Of Active Tb Diseasementioning
confidence: 99%